The Aboriginal Population Health Training Initiative: a NSW Health program established to strengthen the Aboriginal public health workforce - Ben Li; Aaron Cashmore; Dawn Arneman; Wendy Bryan-Clothier; Lisa K McCallum; Andrew Milat (Sax Institute, 2017)
Objectives: Increasing the representation of Aboriginal people in the health workforce can contribute to improving Aboriginal people's health and wellbeing by supporting the provision of more culturally appropriate health programs and services. The Aboriginal Population Health Training Initiative aims to strengthen the Aboriginal public health workforce in New South Wales (NSW), with the long-term goal of improving the health of Aboriginal people. Type of program or service: The program provides comprehensive, competency-based public health training for Aboriginal people. Methods: Participants undertake a series of work placements in public health, and complete a Master of Public Health degree. Results: A 2014 evaluation demonstrated that the program makes an important contribution to strengthening the NSW Aboriginal public health workforce. Trainees reported a high level of satisfaction with the quality of their work placements, the flexibility of the program to support their work and study, and efforts made to ensure the program's cultural safety. The program has a high trainee retention rate (17 of 18 trainees), and all graduates have successfully gained employment within the NSW health system. Lessons learnt: Three key factors contribute to the success of the program: trainees undertake their training within their communities; the structure promotes the direct application of learning through simultaneous work and study; and the NSW Government shows strong leadership and support.